Pengaruh Green Marketing dan Service Quality Terhadap Customer’s Perceived Satisfaction yang Dimediasi Oleh Brand Image - Harjon, Ariescha; Nugroho, Sukmo Hadi (Universitas Trunojoyo Madura, 2024)
This research aims to find out and complement information about the influence of green marketing and service quality on customer's perceived satisfaction mediated by brand image. The research used quantitative methods and survey through online questionnaires towards 712 inpatiens population of private hospitals in East Bekasi in September – November 2023. From 357 respondents, 293 filled out the questionnaire and 257 of them were taken as samples. This research has done through the validity and reliability tests, factor analysis KMO-MSA and Bartlett Test, and path analysis to answer the hypothesis and determine the structural equation model with SmartPLS 3.3.9. The results show that the five hypotheses have been proven positive and significant, namely the direct influence of green marketing on brand image; service quality on brand image; green marketing on customer's perceived satisfaction; service quality on customer's perceived satisfaction; and brand image on customer's perceived satisfaction. Indirectly, brand image acts as a partial mediator that mediates the positive and significant influence of green marketing on customer's perceived satisfaction; and the influence of service quality on customer's perceived satisfaction.